1988
DOI: 10.1103/physrevc.38.135
|View full text |Cite
|
Sign up to set email alerts
|

Preequilibrium emission and incomplete fusion of low and medium mass heavy ion systems

Abstract: The associated phenomena of preequilibrium emission and incomplete fusion in heavy ion collisions at low impact parameter are studied in the context of inverse kinematics and of a symmetrical system. The Ar+ "C, Mg, and 'Sc reactions performed at E40 --27. 5 MeV/nucleon are Ar discussed. Heavy fragments and light particles have been detected inclusively and exclusively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…This results in an intermediate nucleus with mass A = 66 and about 380 MeV excitation energy, i.e. with an average excitation energy of e=5.8 MeV/ nucleon, in good agreement with values found in 4~ fusion reactions on 27A1 [23], 45Sc [6], natNi [5] and 6SZn [24] at bombarding energies 26-35 MeV/u. However, our value substantially exceeds the maximum excitation energy claimed in [9] as limit for residue production in the symmetric Si reaction.…”
Section: Discussionsupporting
confidence: 82%
“…This results in an intermediate nucleus with mass A = 66 and about 380 MeV excitation energy, i.e. with an average excitation energy of e=5.8 MeV/ nucleon, in good agreement with values found in 4~ fusion reactions on 27A1 [23], 45Sc [6], natNi [5] and 6SZn [24] at bombarding energies 26-35 MeV/u. However, our value substantially exceeds the maximum excitation energy claimed in [9] as limit for residue production in the symmetric Si reaction.…”
Section: Discussionsupporting
confidence: 82%
“…It was found that the preequilibrium particles were mostly produced by the lightest partner. This finding was obtained from the masses and velocities of the evaporation residues [t0-13] as well as from a direct measurement of the preequilibrium particles [6][7][8]. The heavy partner participates almost entirely with the fusion mechanism.…”
Section: Introductionmentioning
confidence: 98%
“…With the hypothesis that the clusters, once formed, cannot recombine [15] and generate smaller clusters, the dynamics describe the rate at which the different nuclear species are formed as well as that at which the system deexcites and expands in space. The predictions of this model have been tested with various experimental systems [7,15,16]. Recently, this model has been implemented to simulate the whole decay process on an event by event basis [17].…”
Section: The Pep Calculationmentioning
confidence: 98%
“…One has to keep in mind that these calculations consider a single CN for the initial thermalized system. It is well established, however, that in incomplete fusion a set of nuclear species is formed in this intermediate phase of the reaction [7]. The introduction of such a distribution would appreciably lower the excitation energy of the initial CN.…”
Section: The Heavy Fragmentsmentioning
confidence: 98%
See 1 more Smart Citation